PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM RANGKA MENINGKATKAN PRESTASI SISWA UNTUK MATA PELAJARAN ILMU PENGETAHUAN SOSIAL EKONOMI - Tri Indah Widyastuti (Jurnal Pendidikan Insan Mandiri, 2012)
The objectives of this research to know: (1) The interactive educational situation especially for Social-Economy subject, (2) Students’ understanding in Social-Economy subject and (3) Students’ achievement in Social-Economy subject.This research used classical action research method. It’s done by three cycles in with 43 students of VIII divided into 25 male students and 18 female students.The research’s conclusion was that the application of cooperative Education Model type STAD Based on CTL was significantly proved as to 93,02 % (1) enhance students’ achievement from 60% (cycle 1) to 86,05% (cycle II) then upgraded to 93,02% (cycle III) from 43 students (2) improve students activity and (3) emerge of students’ cooperative skills in subject learning.Keywords: Coopeartive Learning Model, STAD, CTL, Students’ achievement.